Sphaeromacrops Schillhammer new to China with description of a new species (Coleoptera, Staphylinidae) - Tang, Liang; Cheng, Zhi-Fei (Zootaxa, 2020)
Sphaeromacrops Schillhammer, 2001 is recorded from China for the first time, and a new species from Yunnan is described under the name: S. yunnanensis Tang & Cheng sp. n. A key to the species of Sphaeromacrops is provided.